(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the factors influencing the spiritual culture of youth, the ways and means of its enhancement, as well as priority directions in this field. It examines the practical measures implemented by the country’s leadership and their outcomes based on statistical data. Additionally, the article discusses contemporary changes in the spiritual culture of youth, their positive and negative aspects, the importance of considering national cultural characteristics in its development, and the formation of a culture of dialogue through interaction with examples of universal culture.